Building Solidarity with Black Nurses to Dismantle Systemic and Structural Racism in Nursing. (February 2023) - Cooper Brathwaite, Angela; Varsailles, Dania; Haynes, Deborah
Systemic and structural racism in nursing have profound impacts on Black People, Indigenous Peoples, and People of Color. They contributed to underrepresentation in faculty, senior nurse executives, and presidents' positions in academic and healthcare organizations, physical and mental health issues in racialized groups. This quality improvement study described ways in which the Black Nurses Task Force of the Registered Nurses Association of Ontario can build solidarity with nursing and government organizations to dismantle systemic and structural racism in nursing. This study used a structured online survey, comprised of quantitative and qualitative questions. The qualitative data were analyzed using interpretative thematic analysis and the quantitative data were analyzed with descriptive statistics. Findings showed that 88% of participants experienced racism and 63% said racism affected their mental health. Three themes emerged from the qualitative data: Social support for Black nurses, accountability of leaders and solidarity with Black nurses. These findings demonstrated the urgent need to dismantle systemic and structural racism in nursing.